PROJECT: SCREENPLAY FINDING ANDY - Timothy Hendrata; Ribut Basuki (Institute of Research and Community Outreach - Petra Christian University, 2017)
This paper is about my screenplay entitled Finding Andy which I use as my final project. The screenplay itself is a story about a teenage girl who wants to improve her family’s poor communication. For my theory, I use John Gottman’s “The Four Horsemen of the Apocalypse Model” about family conflict. The theory helps me to shape my characters’ behavior towards each others. Since my characters has better relationship even though the brother dies in the end, I tend to use the worst level of family conflict in the beginning of the story and it gradually changes into successful communication which leads to good relationship. The theory helps me to give example of family’s poor communication to the audiences. I also do an observation on some families with poor communications and Rangkah Rejo neighborhood in Eastern Surabaya to build the setting’s circumstances. From this creative work, I expect that it is made into films, like what screenplay is for, so that the audiences realize that this kind of family exists.